Muscular Tuberculosis: A New Case and a Review of the Literature - Zeng, Yanping; Liu, Yin; Xie, Yanchun; Liang, Jingjing; Kuang, Jiabing; Lu, Zuneng; Zhou, Yu (Frontiers in Neurology, 2019)
Objective To investigate the clinical manifestations, underlying diseases, pathological features and therapeutic responses in patients with muscular tuberculosis (MT), which is rare and often misdiagnosed in clinical practice. Methods This study describes a rare MT case that was recently diagnosed in our department. Additionally, eighteen other MT cases retrieved from the PubMed database from 2000 to date are included in this study. The clinical manifestations, areas of residence, underlying diseases, laboratory test results, pathology results and outcomes of the patients were recorded and analysed. Results The MT patients in this study included 13 males and 6 females with an average age of 34.58 years old. Eight patients were from Asia, and 6 patients were from Africa, accounting for the majority of patients, at 73.68%. Underlying diseases included flu-like illness in one patient; chronic renal failure (CRF) in one patient; Sjögren’s syndrome in one patient; systemic lupus erythematosus (SLE), lupus nephropathy and deep vein thrombosis in one patient; and Alzheimer’s disease (AD) and Paget’s disease in one patient. Two patients had a previous history of tuberculosis, and two patients had contact with suspected tuberculosis patients. All patients presented chronic occult onset, with an average of 3 (1.75, 5) months. Six cases had local masses, and 13 cases had swelling as the main clinical manifestations. Twelve patients (63.2%) presented manifestations at single sites, and 7 patients presented manifestations at multiple sites, including the thigh, calf, arm, chest wall, dorsal, psoas, gluteal and forehead muscles. Of the 19 total patients, 13 (68.4%) reported pain, and only eight (42.1%) patients presented tuberculosis symptoms. All patients received laboratory results associated with Mycobacterium tuberculosis infection. Fourteen (73.7%) of the 19 patients underwent skeletal muscle biopsy, where granulomatous inflammation was observed. Eighteen patients were treated with anti-tuberculosis therapies. Sixteen patients improved or recovered after anti-tuberculosis treatment, and unfortunately, two patients died. Conclusion As a kind of systemic disease, MT is mainly characterized by painful or painless muscle masses and swelling at a single site or at multiple sites. Patients with a history of tuberculosis and immune system disease are susceptible to MT.